Peran Penghulu dalam Meningkatkan Kualitas Pelayanan Nikah Rujuk - Zubir, Muhammad (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2023)
This article describes that the Office of Religious Affairs (KUA) is a work unit of the Ministry of Religion at the District level in serving the needs of the community. One of the 10 most important tasks and functions of the KUA is: